GE_GERICHTE C/4669/2013 vom 11. April 2014 - GE Cour de justice (2014)
PROTECTION DE L'UNION CONJUGALE; REVENU HYPOTHÉTIQUE; RÉTROACTIVITÉ; MESURE D'ÉLOIGNEMENT(EN GÉNÉRAL) | CC.28b.1; CC.172.3; CC.176; CPC.315.1; CPC.317.1